A 10 cm pedunculated duodenal Brunner gland hamartoma, case report and literature review. (November 2022) - Alsugair, Ziyad; Lavrut, Pierre Marie; Chassagne, Lisa
Abstract: Introduction: Brunner gland hamartoma is rare duodenal neoplasm. These benign lesions are usually presented by upper gastrointestinal bleeding and sometimes extend to cause intestinal obstruction. Presentation of the case: We report a case of a 43-year-old male patient manifested with iron deficiency anemia. Upon investigations, computed topography (CT) scan found a dilated first part of the duodenum with presence of large pedunculated polyp. The histopathological examination revealed a submucosal lobular proliferation of duodenal Brunner's gland separated by a fine fibrous septum. No dysplastic signs were observed. Immunohistochemical studies confirmed the nature of the glands and reveled absence of Helicobacter pylori gastritis. Diagnosis was confirmed. Discussion: Brunner glands hamartomas are rare tumors. They are commonly presented by upper GI bleeding and intestinal obstruction. The pathogenesis remains unclear. They are usually located in the first part (bulb) of the duodenum. Mucosal irritation and Helicobacter pylori infection are suggested causes. Different surgical and endoscopical modalities are applied in the management depending on the size and location of the mass. In our case, the tumor was removed by Endoscopic submucosal dissection. Conclusion: Brunner gland hamartoma is a rare usually benign tumor. Presented clinically by upper GI bleeding and obstruction. Histopathologically Brunner gland Hamartoma characterized by lobular proliferation of Brunner gland associated with presence of other mature tissues. Although these tumors are benign it carries a minor risk of malignant transformation. Highlights: Duodenal Brunner's gland hamartoma is a rare benign tumor accounts for less than 1% of the primary tumors of the small intestine. Brunner's gland hamartoma is a submucosal proliferative dysmoembryoplastic lesion of the duodenum. Different surgical and endoscopical modalities are applied in the management depending on the size and location of the mass. Growth of the benign proliferative lesions of Brunner's glands, mucosal ulcers may develop, leading to gastric foveolar metaplasia and malignant transformation.